Reproducibility of a food frequency questionnaire for adolescents Reprodutibilidade de um questionário de freqüência alimentar para adolescentes - Dirce Maria Lobo Marchioni; Silvia Maria Voci; Flávia Emília Leite de Lima; Regina Mara Fisberg; Betzabeth Slater (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
To assess the reproducibility of a validated 76-item food frequency questionnaire designed to estimate diet in adolescents (Adolescent Food Frequency Questionnaire - AFFQ) in the city of Sao Paulo, Brazil, a test-retest study was conducted (n = 49). Intraclass correlation coefficient (ICC), weighted kappa, and percentage of agreement were used in both crude and energy-adjusted nutrient intakes. Bland Altman plots were used to examine the limits of agreement for energy and macronutrients. The ICC ranged from 0.48 (carbohydrates) to 0.65 (vitamin C) in crude values and from 0.25 (total fat) to 0.58 (vitamin C) in adjusted values. Kappa values ranged from 0.28 (protein and fiber) to 0.56 (unsaturated fat). Bland Altman showed a trend towards larger difference in energy according to increased intake values and a bias towards extreme values for fat intake. The percent of individuals classified in the same category on the two occasions was on average 54.2%. By conclusion, the Adolescent Food Frequency Questionnaire showed reasonable reproducibility and can be used in studies that aim to classify groups into intake categories. Para avaliar a reprodutibilidade de um Questionário de Freqüência Alimentar para Adolescentes (QFAA), 76 itens, validado, desenvolvido para estimar a dieta habitual de adolescentes em São Paulo, Brasil, foi conduzido um estudo do tipo teste-reteste (n = 49). Utilizaram-se o coeficiente de correlação intraclasse (CCI), o kappa ponderado e a porcentagem de concordância para os valores de ingestão brutos e ajustados pela energia. Os limites de concordância para energia e macronutrientes foram examinados pelos gráficos de Bland Altman. O CCI variou de 0,48 (carboidratos) a 0,65 (vitamina C) para os nutrientes brutos e de 0,25 (lipídios totais) a 0,58 (vitamina C) para os ajustados. Os valores do kappa variaram de 0,28 (proteínas e fibras) a 0,56 (lipídios insaturados). O gráfico de Bland Altman evidenciou tendência à maior diferença para energia conforme o aumento dos valores de ingestão e para lipídios com os valores extremos. A porcentagem de indivíduos classificados na mesma categoria foi em média 54,2%. Conclui-se que o QFAA apresentou razoável reprodutibilidade e pode ser utilizado em estudos que objetivam classificar os indivíduos em categorias de consumo.